Will the Doha Round lead to preference erosion? - Amiti, Mary (2007)
Assesses the effects of reducing tariffs under the Doha Round on market access for developing countries. Shows that for many developing countries actual preferential access is less generous than it appears because of low product coverage rules of origin. Indicates that the largest gains in market access are generated by higher tariff cuts in agriculture.